2017
DOI: 10.4103/0976-9668.210018
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biophysical characterization of cajanus cajan protease inhibitor

Abstract: Context:A large number of studies have proven that Protease inhibitors (PIs), specifically serine protease inhibitors, show immense divergence in regulation of proteolysis by targeting their specific proteases and hence, they play a key role in healthcare.Objective:We aimed to access in-vitro anticancer potential of PI from Cajanus cajan (CCPI). Also, crystallization of CCPI was targetted alongwith structure determination and its structure-function relationship.Materials and Methods:CCPI was purified from Caja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The methanol extract of the bark of Guibourtia tessmannii (Harms) J.Leonard (from Cameroon) has shown antiproliferative activity against cervical cancer cells (Kuete et al, 2013), while serine protease inhibitors from Cajanus cajan (L.) Millsp. seeds (also known as the pigeon pea) demonstrated anticancer potential (Shamsi et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The methanol extract of the bark of Guibourtia tessmannii (Harms) J.Leonard (from Cameroon) has shown antiproliferative activity against cervical cancer cells (Kuete et al, 2013), while serine protease inhibitors from Cajanus cajan (L.) Millsp. seeds (also known as the pigeon pea) demonstrated anticancer potential (Shamsi et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro and in vivo studies showed that PPIs are toxic to larval gut proteases, causing digestion defects and disruption of amino acid absorption. Besides, PPIs result in retarded growth and development of the larvae, consequently affecting the fecundity and productivity of the moth [13]. Similarly, C. scarabaeoides accession IBS 3471 contained the largest quantities of cysteine proteinase inhibitors and lectin-domain containing receptor kinases ( Figure 5), resulting in the most significant inhibition to H. armigera larval growth (Figures 1, 3 and 4; Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%